'Comme une chanson de Bruant': marginality, nostalgia and protest during the 1968 years. Issue 1 (February 2021) - Cannon, James
Abstract: The '1968 years' (1968–1981) witnessed a resurgence of interest in the late 19th-century singer-songwriter and cabaret performer Aristide Bruant (1851–1925). This article explores the social and cultural origins of this Bruant 'moment', arguing that it was linked both to a culture of marginality that emerged during the events of May–June 1968 and to a culture of nostalgia ('la mode rétro') first identified in 1973. It focuses on five performers who revived or renewed Bruant's legacy during the 1968 years: Mouloudji, Francesca Solleville, Marc Ogeret, François Béranger and Renaud.